PPE Compliance and Visual Impairment Among Welders in Johan Pahlawan, West Aceh: An Occupational Health Study in 2019 - Muttaqin ZA; Khairunnas Khairunnas; Jun Musnadi Is (Mitra Akademia Indonesia, 2026)
The Minister of Health has mandated that all workplaces implement occupational health initiatives to prevent adverse health outcomes among workers, their families, communities, and the surrounding environment. This study aimed to analyze the extent of the association between Personal Protective Equipment (PPE) compliance and visual impairment among welding workshop workers in Johan Pahlawan District. Utilizing a quantitative approach, data were evaluated using univariate and bivariate analyses. The results demonstrated a significant association between knowledge and visual impairment (p = 0.000, OR = 1.081). Similarly, a significant correlation was observed between worker attitudes and visual disorders (p = 0.0000, OR= 0.788). Furthermore, actions regarding PPE usage were significantly associated with visual impairment (p = 0.0000, OR = 0.925). Based on these findings, it is suggested that workshop owners enhance monitoring, counseling, and safety guidance regarding the correct usage, maintenance, and storage of PPE. Workers with high knowledge levels should maintain safe practices to foster better safety attitudes during welding operations. Finally, relevant government agencies can utilize these findings as a reference to address occupational safety issues more comprehensively.